ChemInform Abstract: Mono‐ and Di‐Lanthanide Derivatives of 22‐Tungsto‐2‐antimonate(III), [Ln(H2O)4Sb2W21O72 (OH)]10‐ and [Ln2 (H2O)8Sb2W20O70] 8‐. Issue 6 (11th February 2014) - Ismail, Amal H.; Bassil, Bassem S.; Roemer, Isabella; Kortz, Ulrich
Abstract The structures of the mono‐ and di‐lanthanoid polyoxotungstate derivatives are determined by single crystal XRD.